2002
DOI: 10.1016/s0375-9601(02)00731-4
|View full text |Cite
|
Sign up to set email alerts
|

Moving breathers in a bent DNA model

Abstract: We study the properties of moving breathers in a bent DNA model with short range interaction, due to the stacking of the base pairs, and long range interaction, due to the finite dipole moment of the bonds within each base pair. We show that the movement of a breather is hindered by the bending of the chain analogously to a particle in a potential barrier.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 29 publications
2
34
0
Order By: Relevance
“…[15]: if K Ͻ U c , the value of K is fixed and X o is the point where the breather is reflected (turning point), then K = U͑X o ͒.…”
Section: A Morse Chain: Bend-induced Potential Barriermentioning
confidence: 99%
“…[15]: if K Ͻ U c , the value of K is fixed and X o is the point where the breather is reflected (turning point), then K = U͑X o ͒.…”
Section: A Morse Chain: Bend-induced Potential Barriermentioning
confidence: 99%
“…[23,30,36]. The dimensionless stacking parameter then becomes C = 0.075, which we use throughout the paper.…”
Section: ͑1͒mentioning
confidence: 99%
“…Recently, both long-range dipole-dipole interaction [23,24], helicity [25,26] and curvature [27][28][29] have been included in the nonlinear transport theory, as well as combinations of these effects [30][31][32][33][34]. It has been shown that chain geometry induces effects similar to those of impurities [27][28][29]32].…”
Section: Introductionmentioning
confidence: 99%
“…This model describes, by a simplified approach, the hydrogen bond and has been applied successfully to many applications such as energy localization [15] and calculation of solitonic speed [16]. In this model, the double strand corresponds to a Klein-Gordon chain, the variable parameters are the distances between nucleotides within each base pair, and only short-range interactions are considered because of the stacking coupling [17]. It is well known that the Peyrard-Bishop (PB) model can produce solitons due to the balanced competition between dispersion and nonlinear effects [18][19][20].…”
Section: Introductionmentioning
confidence: 99%